2006
DOI: 10.1016/s1556-0864(15)30415-9
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib (IRESSA) in Patients of Asian Origin with Refractory Advanced Non-small Cell Lung Cancer: Subset Analysis from the ISEL Study

Abstract: Introduction:The IRESSA Survival Evaluation in Lung Cancer (ISEL) phase III study compared the efficacy of gefitinib (IRESSA) versus placebo in patients with refractory advanced non-small cell lung cancer (NSCLC). Although a statistically significant difference in survival was not seen between gefitinib and placebo in the overall ISEL population, preplanned subset analyses demonstrated a significant survival benefit in patients who had never smoked and in patients of Asian origin. Methods: In ISEL, 1692 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 28 publications
1
46
0
1
Order By: Relevance
“…Two drugs, erlotinib (Tarceva) and gefitinib (Iressa; AstraZeneca Inc., Menchester, UK), have been shown to have survival benefit in Caucasians and Asians, respectively, when compared to placebo in controlled, double-blinded, randomized phase III trials. [3,4] These two EGFR-TKIs disrupt EGFR signaling by competing with adenosine triphosphate (ATP) for the binding sites at tyrosine kinase domain, and result in inhibition of phosphorylation and the downstream signaling network. These EGFR-TKIs are only effective to a subgroup of NSCLC patients and act faster than conventional chemotherapy, but have relatively mild side effects.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…Two drugs, erlotinib (Tarceva) and gefitinib (Iressa; AstraZeneca Inc., Menchester, UK), have been shown to have survival benefit in Caucasians and Asians, respectively, when compared to placebo in controlled, double-blinded, randomized phase III trials. [3,4] These two EGFR-TKIs disrupt EGFR signaling by competing with adenosine triphosphate (ATP) for the binding sites at tyrosine kinase domain, and result in inhibition of phosphorylation and the downstream signaling network. These EGFR-TKIs are only effective to a subgroup of NSCLC patients and act faster than conventional chemotherapy, but have relatively mild side effects.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…Studija ISEL (Iressa Survival Evaluation in Lung cancer) bila je studija III faze kliničkog ispitivanja 250 mg gefitiniba primenjenog kao druga ili treća linija lečenja bolesnika sa lokalno uznapredovalim ili metastatskim NSCLC rezistentnim na prethodno primljenu standardnu hemioterapiju (9). Zaključci iz ovih studija bili su da najveću korist od gefitiniba (u standardnoj dozi od 250 mg dnevno) u odnosu na placebo, imaju nepušači, žene, oboleli od adenokarcinoma i bolesnici azijske populacije.…”
Section: Egfrunclassified
“…In addition, TKIs responsive patients also showed different sensitivity to the treatment. These findings indicated that other causes might also contribute to the intrinsic resistance (8)(9)(10). Therefore, completely understanding of the causes for responsiveness to EGFR TKIs is worth pursuing to improve the clinical benefits of targeted therapies.…”
Section: Introductionmentioning
confidence: 99%